Study and Control of qZ Source Inverter for Grid-Connected Photovoltaic System - Cheriguene Mounir; Benbrahim Samah Hadil; HADJADJ Merouane (UNIVERSITY OF Ammar Telidji LAGHOUAT. FACULTY OF TECHNOLOGY. DEPARTMENT OF ELECTROTECHNICS, 2025)
This thesis presents a comprehensive study and control strategy for a quasi-Z-source inverter (qZSI) in a grid-connected photovoltaic (PV) system. Various Maximum Power Point Tracking (MPPT) algorithms including Perturb and Observe (P&O), Incremen tal Conductance (INC), Hill Climb (HC), and Fuzzy Logic Controller (FLC) were im plemented and compared. System performance was evaluated for resistive load, single phase, and three-phase qZSI configurations considering tracking efficiency, response time, oscillations, robustness, and total harmonic distortion (THD). The FLC-based MPPT demonstrated superior performance across scenarios, making it a promising candidate for practical PV grid-tied applications.
Specialization: Renewable Energies